Emotional Determination of Students’ Psychological Health: Some aspects of the Problem - Kichuk, Antonina (Psychological Prospects Journal, 2019)
The issue of psychological peculiarity of the urgent present-day phenomenon is raised since the matter is about psychological health – standard and existential value of a personality throughout one’s course of life. The result of the analysis of science foundation where problematic issues concerning personality’s psychological health are being directly or indirectly interpreted makes it possible to state that modern students’ psychological health forms the area of psychological and pedagogical losses. It is determined by both the absence of psychological health theory of a person in a period of young adulthood and underestimation of emotional constituent peculiarity of modern students’ health in psychological sphere. It is emphasized that urgency of a defined perspective of the problem raised is evident inasmuch as psychological health is mainly interpreted by modern researchers as integral personality feature that positively correlates with both a personality’s subjective quality of life and his achievement of success in life. The constructiveness of logical and semantic pattern is argued which makes it possible to extend the scientific conception about phenomenology of students’ psychological health particularly according to characteristics such as personality orientation, cognitive dominant, communicative component, regulatory constituent and component of key qualifications. All the above mentioned allows us to evaluate in a new way the significance of emotions and feelings self-creation, level experience measurement, the role of a person‘s emotional willingness for changing during one’s life, the importance of self-knowledge and spiritual experience. The analysis of some empirical studies of scientists indicates the vectors of further scientific exploration concerning the problematic field of students’ psychological health. Integrated study of the specific character of emotional component of a teen-age personality’s health in psychological sphere as one of the direction is singled out.